2008
DOI: 10.1177/0193945908319991
|View full text |Cite
|
Sign up to set email alerts
|

Qigong Improving Physical Status in Middle-Aged Women

Abstract: Regular exercise has been shown to benefit its practitioners and prevent and control diseases. Muscle/Tendon Change Classic (MTCC) qigong, characterized by simple, slow, and full-body exercise, is appropriate for the middle-age population. This study aims to evaluate the effect of the MTCC qigong program in improving physical status for middle-aged women. A quasi-experimental design was used. The experimental group (n = 37) received an 8-week MTCC qigong program, whereas the control group (n = 34) received non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…3,24,25 Many researchers have reported that TCQ might be beneficial for improving exercise tolerance in both healthy people and those with chronic diseases. [26][27][28][29][30] According to the results of the present review, TCQ appears to demonstrate a greater improvement in physical activity such as exercise tolerance than intervention without exercise training. However, it cannot be confirmed that TCQ are the better complementary treatments for physical activity in COPD rehabilitation than other exercise training forms.…”
Section: Discussionmentioning
confidence: 59%
“…3,24,25 Many researchers have reported that TCQ might be beneficial for improving exercise tolerance in both healthy people and those with chronic diseases. [26][27][28][29][30] According to the results of the present review, TCQ appears to demonstrate a greater improvement in physical activity such as exercise tolerance than intervention without exercise training. However, it cannot be confirmed that TCQ are the better complementary treatments for physical activity in COPD rehabilitation than other exercise training forms.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, a previous study demonstrated that 2 months of qigong practice failed to improve the bone strength (measured using ultrasound) of middle-aged women. 26 However, a longer duration (>3 months) of qigong practice can maintain the overall BMD and reduce the levels of interleukin-6 (a marker of bone resorption) in the same population. 14 Regarding the healthy controls, we found that their BMD at different body sites was similar to that of the breast cancer survivors who practiced qigong and also to that of breast cancer survivors who did not practice qigong.…”
Section: Discussionmentioning
confidence: 99%
“…As well, Tsai et al [ 41 ] found Qigong improved the physical status including muscle endurance, and waist-to-hip ratio and body fat of participants. Here the method used was described as the Muscle/Tendon Change Classic, which is characterized by simple, slow, and full body exercises that seemed to help the experimental group to show health preserving effects after 8 weeks of training.…”
Section: Additional Research Evidencementioning
confidence: 92%